2007
DOI: 10.3133/ofr20071047srp105
|View full text |Cite
|
Sign up to set email alerts
|

Denudation and uplift of the Mawson Escarpment (eastern Lambert Graben, Antarctica) as indicated by apatite fission track data and geomorphological observation

Abstract: Analysis of three vertical profiles from the southern Mawson Escarpment (Lambert Graben) reveals apatite fission track (AFT) ages ranging from 102±20 to 287±23 Ma and mean lengths of 12.2 to 13.0 µm. Quantitative thermal histories derived from these data consistently indicate onset of slow cooling below 110°C began sometime prior to 300 Ma, and a second stage of rapid cooling from paleotemperatures up to ≤100°C to surface temperatures occurred in the Late Cretaceous -Paleocene. The first cooling phase refers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…time for the Gamburtsev Mountains and East Antarctic rift system by Ferraccioli et al [2011]. [27] A number of authors have proposed a second period of rifting in the Lambert Graben area during the Cretaceous associated with the final breakup of Gondwana [Arne, 1994;Ferraccioli et al, 2011;Lisker et al, 2003Lisker et al, , 2007aLisker et al, , 2007b, which Lisker et al [2003] use to explain their apatite fission track data. However, the zircon fission track cooling ages of $120 Ma form a single well-defined peak more consistent with local resetting related to alkaline mafic magmatism of this age in the Beaver Lake area of the Northern Prince Charles Mountains [Coffin et al, 2002].…”
Section: Zircon Fission Trackmentioning
confidence: 99%
See 1 more Smart Citation
“…time for the Gamburtsev Mountains and East Antarctic rift system by Ferraccioli et al [2011]. [27] A number of authors have proposed a second period of rifting in the Lambert Graben area during the Cretaceous associated with the final breakup of Gondwana [Arne, 1994;Ferraccioli et al, 2011;Lisker et al, 2003Lisker et al, , 2007aLisker et al, , 2007b, which Lisker et al [2003] use to explain their apatite fission track data. However, the zircon fission track cooling ages of $120 Ma form a single well-defined peak more consistent with local resetting related to alkaline mafic magmatism of this age in the Beaver Lake area of the Northern Prince Charles Mountains [Coffin et al, 2002].…”
Section: Zircon Fission Trackmentioning
confidence: 99%
“…The Lambert Graben was formed primarily by Permo-Triassic rifting [Cox et al, 2010;Kurinin and Grikurov, 1982;Lisker, 2002;Lisker et al, 2007b] and extends $500 km to the south of Prydz Bay into the interior of the continent [O'Brien et al, 2007]. Local, small-volume mafic magmatism associated with the break-up of Gondwana occurred in the Lambert Graben/Prydz Bay area during the early to mid Cretaceous [Arne, 1994;Coffin et al, 2002;Collerson and Sheraton, 1986;Hambrey and McKelvey, 2000;Jamieson et al, 2005;Kurinin and Grikurov, 1982;Lisker et al, 2003Lisker et al, , 2007aLisker et al, , 2007b. [4] In addition to hosting an ice stream currently draining a large portion of the EAIS, the Lambert Graben was an important drainage route for fluvial systems prior to the onset of glaciation in East Antarctica.…”
Section: Introductionmentioning
confidence: 99%
“…It provides, firstly, a better model of the initial basin morphology, but also helps to understand erosion processes in the Denman and Scott ice streams. Full details of the method are provided in the supporting information [ Jacobs and Lisker , ; Lisker et al ., , ; Mory and Iasky , ; Olierook et al ., ; Taylor et al ., ].…”
Section: Geophysical Modelingmentioning
confidence: 99%
“…Bedrock elevations on both grids are contoured at 1 km intervals. Colored circles show published bedrock AFT and AHe data from the Lambert Rift area (Arne, 1994; Lisker et al, 2003; Lisker, Gibson, et al, 2007), Vestfold Hills (Lisker, Wilson, & Gibson, 2007), and Terre Adélie/George V Land (Lisker & Olesch, 2003; Rolland et al, 2019) as well as reconnaissance AFT data of Arne et al (1993). Sedimentary basin‐bounding faults in the EARS (Ferraccioli et al, 2011), Knox Rift (Maritati et al, 2016), Aurora and Vincennes Subglacial Basins, (Aitken, Roberts, et al, 2016), Wilkes Subglacial Basin (Paxman, Jamieson, Ferraccioli, et al, 2019, and references therein) are highlighted in red; dashed black lines correspond to the inferred path the Mirny Fault (Daczko et al, 2018) and Gamburtsev Suture (Ferraccioli et al, 2011), which together represent the paleoplate boundary between Indo‐Antarctica and Australo‐Antarctica (Mulder et al, 2019); dashed box in panel (a) indicates a detail of the Bunger Hills region shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…Existing LTT data from Precambrian basement outcrops in the Indo‐Antarctic and Australo‐Antarctic domains suggest major cooling of East Antarctic basement during the Paleozoic–Mesozoic (Figure 1); however, the significance of these observed Paleozoic–Mesozoic tectonothermal events across interior East Antarctica, and any link in establishing the different topographic response of each domain, remains elusive. In the Indo‐Antarctic domain, apatite fission track (AFT) data from basement rocks in the northern Prince Charles Mountains (PCM) and Vestfold Hills record cooling associated with up to 5 km of basement exhumation during two discrete phases of continental rifting in the Lambert Rift (Arne, 1994; Lisker et al, 2003; Lisker, Gibson, et al, 2007; Lisker, Wilson, & Gibson, 2007) and broader East Antarctic Rift System (EARS; Ferraccioli et al, 2011) in the Late Paleozoic–Triassic (~310–200 Ma) and Cretaceous (~120–100 Ma). In the Australo‐Antarctic domain west of the Transantarctic Mountains (TAM), AFT and apatite (U‐Th)/He (AHe) data record a single Late Paleozoic–Triassic cooling event between ~350 and 200 Ma.…”
Section: Introductionmentioning
confidence: 99%